Study On The Mechanism Of Panic Buying Under Omicron Virus Impact (Journal of Pharmaceutical Negative Results, 2023)
China has shown strong social cohesion and epidemic prevention and control actions in the face of the sudden new crown epidemic. This study uses questionnaire survey (N=208) data to investigate the important role of group factors and individual anxiety as mediating variables in the panic buying of the new crown epidemic through an empirical study. It was found that group factors significantly and positively influenced panic buying and individual anxiety significantly and positively influenced panic buying; government control significantly influenced panic buying through the mediating effect of group factors and individual anxiety. By exploring the mechanism of government control on panic buying and the role of group factors and individual anxiety as mediating variables, the study proposes thoughts on the way government control is guided in public crisis events. Government control is a policy risk, which affects individual anxiety through group factors and thus panic buying, and panic buying can lead to scarcity of goods and thus market risk.